Approaches to increase mechanistic understanding and aid in the selection of precipitation inhibitors for supersaturating formulations – a PEARRL review. (16th May 2018) - Price, Daniel J.; Ditzinger, Felix; Koehl, Niklas J.; Jankovic, Sandra; Tsakiridou, Georgia; Nair, Anita; Holm, René; Kuentz, Martin; Dressman, Jennifer B.; Saal, Christoph
Abstract: Objectives: Supersaturating formulations hold great promise for delivery of poorly soluble active pharmaceutical ingredients (APIs). To profit from supersaturating formulations, precipitation is hindered with precipitation inhibitors (PIs), maintaining drug concentrations for as long as possible. This review provides a brief overview of supersaturation and precipitation, focusing on precipitation inhibition. Trial‐and‐error PI selection will be examined alongside established PI screening techniques. Primarily, however, this review will focus on recent advances that utilise advanced analytical techniques to increase mechanistic understanding of PI action and systematic PI selection. Key findings: Advances in mechanistic understanding have been made possible by the use of analytical tools such as spectroscopy, microscopy and mathematical and molecular modelling, which have been reviewed herein. Using these techniques, PI selection can be guided by molecular rationale. However, more work is required to see widespread application of such an approach for PI selection. Summary: Precipitation inhibitors are becoming increasingly important in enabling formulations. Trial‐and‐error approaches have seen success thus far. However, it is essential to learn more about the mode of action of PIs if the most optimal formulations are to be realised. Robust analytical tools, and the knowledge of where and how they can be applied, will be essential in this endeavour.